2010
DOI: 10.1007/s10295-010-0808-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid production by Rhodosporidium toruloides Y4 using different substrate feeding strategies

Abstract: Microbial lipid is a potential alternative feedstock for the biodiesel industry. New culture strategies remain to be developed to improve the economics of microbial lipid technology. This work describes lipid production by the oleaginous yeast Rhodosporidium toruloides Y4 using a 15-l bioreactor with diVerent substrate feeding strategies. Among these strategies, the intermittent feeding mode gave a lipid productivity of 0.36 g l ¡1 h ¡1 , whereas the constant glucose concentration II (CC-II) mode gave the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 24 publications
9
96
1
4
Order By: Relevance
“…A similar phenomenon has been previously observed in another study [29], which also used a repeat batch process for microbial lipid production. To explain this phenomenon, the profile of VFA consumption, TN (Total nitrogen), TOC (Total organic carbon), and C/N (Carbon/Nitrogen) ratio were also measured.…”
Section: Cell Growth and Lipid Accumulation By C Curvatus Using Carbsupporting
confidence: 72%
“…A similar phenomenon has been previously observed in another study [29], which also used a repeat batch process for microbial lipid production. To explain this phenomenon, the profile of VFA consumption, TN (Total nitrogen), TOC (Total organic carbon), and C/N (Carbon/Nitrogen) ratio were also measured.…”
Section: Cell Growth and Lipid Accumulation By C Curvatus Using Carbsupporting
confidence: 72%
“…Very high lipid content was obtained when it was cultivated in media with an initial carbon-to-nitrogen (C/N) ratio of 77 (Turcotte and Kosaric, 1989). We demonstrated that high lipid titer could be achieved by fed-batch and repeated fed-batch culture of R. toruloides under nitrogen limitation conditions (Li et al, 2007;Zhao et al, 2010). During the cultivation process, cell growth was accompanied with lipid accumulation.…”
Section: Introductionmentioning
confidence: 95%
“…While the ratio C/N plays the most important role in lipid accumulation, the culture mode is also of special interest. For this reason, Zhao et al (2011) used different feeding strategies with yeast R toruloides Y4 and concluded that the fed-batch strategy exhibited the largest oil accumulation potential under large-scale production plant, while keeping the residual glucose concentration to 5 g/L of carbon source and the fed-batch cycles were multiple times repeated. Authors removed the majority of the mature culture at the end of each cycle, keeping 900 ml of the culture in the bioreactor.…”
Section: Yeastmentioning
confidence: 99%